IMPLEMENTASI PBL BERBASIS CHROMEBOOK DENGAN KONTEKS LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Wahyudi, Muhammad Ilham (De Fermat : Jurnal Pendidikan Matematika, 2026)
This classroom action research investigated the use of Chromebook-supported Problem-Based Learning (PBL) to enhance students’ mathematical critical thinking on the topic of relations and functions. The study was conducted at SMP Negeri 3 Muara Wis with 16 eighth-grade students across two action cycles using the Kemmis and McTaggart model. Data were collected through analytic rubrics for clarification, interpretation, inference, and evaluation, complemented by classroom observations and students’ digital artifacts. The action’s success indicator was defined by achieving a minimum class average target of 75% across all critical thinking indicators. Findings show an improvement in overall critical-thinking performance from 36.6% in the pre-cycle to 79.5% in Cycle II, with the largest gains in inference and evaluation. The integration of local contextual problems related to fishermen’s activities, alongside collaborative digital workflows, strengthened students’ reasoning and argumentation. The study concludes that PBL supported by simple digital tools can effectively improve mathematical critical thinking when accompanied by structured scaffolding and systematic reflection.